Enhanced Cycling Stability of Al-Doped Li1.20Mn0.52-x Al x Ni0.20Co0.08O2 as a Cathode Material for Li-Ion Batteries by a Supercritical-CO2-Assisted Method - Yalcin, Ali; Mehmet, Oguz Guler; Demir, Muslum; Gonen, Mehmet; Akgun, Mesut (AMER CHEMICAL SOC, 2024)
Lithium-rich layered oxide materials (Li-NMC) are considered a potential cathode material for next-generation batteries, thanks to their high theoretical specific capacity. Large potential drop and capacity loss after long cycles are the main obstacles to expanding commercial utilization of Li-NMC. In the past decade, great efforts have been made to overcome those issues of Li-NMCs. In this study, Al-doped Li1.20Mn0.52-x Al x Ni0.20Co0.08O2 cathode materials are for the first time synthesized by a supercritical-CO2-assisted method. Upon the electrochemical tests of Al-doped Li-rich NMCs, the optimal initial charge/discharge profile is obtained for the Li-NMC-Al02 cathode with 374.6/247.5 mAh/g compared with that of 320.7/235.1 mAh/g for the pristine Li-NMC-Al00 sample at the C/20 rate. In addition, the Li-NMC-Al02 cathode shows an enhanced rate-capability performance compared to the pristine sample at relatively low rates. When the current density is increased from C/10 to 3C, the charge/discharge capacity values of the Li-NMC-Al02 cathode are measured as 249.88/105.84 mAh/g. Last but not least, Li-NMC-Al02 demonstrates an excellent energy retention of 92.32%, which is notably higher than that of pristine Li-NMC-Al00 (86.4%) after 120 cycles at the C/20 rate. Overall, the present fabrication and doping strategy opens a new avenue for commercialization of Li-NMC cathode materials.
Keywords: ELECTROCHEMICAL PERFORMANCE; HIGH-CAPACITY; BORIC-ACID; OXIDE; NI; CO; Chemistry